2004
DOI: 10.1590/s1676-56482004000100005
|View full text |Cite
|
Sign up to set email alerts
|

Tomada de decisão em futuros agropecuários com modelos de previsão de séries temporais

Abstract: Este artigo trata da aplicabilidade de modelos de previsão de séries temporais como ferramenta de decisão de compra e venda de contratos futuros de boi gordo, café e soja na BM&F, em datas próximas ao vencimento. Os modelos estudados são: ARIMA, Redes Neurais Artificiais, e Modelos Lineares Dinâmicos. Os dados correspondem às cotações semanais, nos mercados físico e futuro, entre 1996 e 1999. O objetivo consiste em calcular os retornos médios dos modelos em operações no mercado futuro de boi gordo, café e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
19

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 13 publications
0
4
0
19
Order By: Relevance
“…These authors confirmed the forecasting effectiveness for monthly sugar prices with the highest predictive approximation in recent months. In forecasting the weekly coffee and soybean prices, BRESSAN (2004) presented evidence favorable to the use of the classic (autoregressive) and ANN models as decision tools in agricultural negotiations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors confirmed the forecasting effectiveness for monthly sugar prices with the highest predictive approximation in recent months. In forecasting the weekly coffee and soybean prices, BRESSAN (2004) presented evidence favorable to the use of the classic (autoregressive) and ANN models as decision tools in agricultural negotiations.…”
Section: Resultsmentioning
confidence: 99%
“…As the package allows changing the number of neurons, models with 5, 10, 15, 20, and 25 neurons were used Number of neurons was changed during the training phase, as in the studies of SOBREIRO et al (2008), BRESSAN (2004), andFERREIRA et al (2011).…”
Section: Application Of Statistical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nas últimas décadas, a busca por fatores que interferem nas condições climáticas e suas consequências para a humanidade, tem sido objeto de estudo por diversos pesquisadores (MENDONÇA, 2005;CASAGRANDE et al, 2011;QUEIROZ e COSTA, 2012;SIQUEIRA JÚNIOR, TOMASELLA e RODRIGUEZ, 2015). Entender os comportamentos climáticos de uma determinada região é de suma importância para o desenvolvimento de diversos setores da atividade humana; por exemplo, o setor agrícola, ambiental ou econômico.…”
Section: Introductionunclassified
“…Nestas redes, a informação é armazenada nos pesos, assim, estes pesos são alterados quando ocorre "aprendizado". Na agricultura, são utilizadas, por exemplo, na análise de dados agrometeorológicos [6], na classificação automática de cultivares [7], no auxílio à tomada de decisão [8], entre outros.…”
Section: Introductionunclassified